Unveiling the orbital-selective electronic band reconstruction through the structural phase transition in TaTe_{2} - Natsuki Mitsuishi; Yusuke Sugita; Tomoki Akiba; Yuki Takahashi; Masato Sakano; Koji Horiba; Hiroshi Kumigashira; Hidefumi Takahashi; Shintaro Ishiwata; Yukitoshi Motome; Kyoko Ishizaka (Physical Review Research, 2024)
Tantalum ditelluride (TaTe_{2}) belongs to the family of layered transition metal dichalcogenides but exhibits a unique structural phase transition at around 170 K that accompanies the rearrangement of the Ta atomic network from a “ribbon chain” to a “butterfly-like” pattern. While multiple mechanisms including Fermi surface nesting and chemical bonding instabilities have been intensively discussed, the origin of this transition remains elusive. Here we investigate the electronic structure of single-crystalline TaTe_{2} with a particular focus on its modifications through the phase transition, by employing core-level and angle-resolved photoemission spectroscopy combined with first-principles calculations. Temperature-dependent core-level spectroscopy demonstrates a splitting of the Ta 4f core-level spectra through the phase transition indicative of the Ta-dominated electronic state reconstruction. Low-energy electronic state measurements further reveal an unusual kink-like band reconstruction occurring at the Brillouin zone boundary, which cannot be explained by Fermi surface nesting or band-folding effects. On the basis of the orbital-projected band calculations, this band reconstruction is mainly attributed to the modifications of specific Ta 5d states, namely, the d_{XY} orbitals (the ones elongating along the ribbon chains) at the center Ta sites of the ribbon chains. The present results highlight the strong orbital-dependent electronic state reconstruction through the phase transition in this system and provide fundamental insights towards understanding complex electron-lattice-bond coupled phenomena.